Performan Ayam Broiler dengan Penambahan Tepung Daun dalam Pakan - Ari Kusuma Wati; Zuprizal Zuprizal; Kustantinah Kustantinah; Edwin Indarto; Nanung Danar Dono; Wihandoyo Wihandoyo (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2018)
The aim of this research was studied the effect of addition leaf meal in feed on performance of broiler chicken. The research used five groups of treatments, those were 0.0, 2.5, 5.0, 7.5, and 10.0% calliandra leaf meal on feed. Each treatment were consists of three replications. The data of  feed intake, average daily gain, protein intake, energy intake and feed conversion ratio were taken every week for 4 weeks. The collected data were analyzed using Completely Randomized Design (CRD) and continued by tested using Duncan’s New Multiple Range Test (DMRT). The results showed that the addition of calliandra leaf meal significantly (P<0.05) on feed intake, body weight gain, protein intake, energy intake and feed conversion ratio. The result of this study  can be concluded that utilization of calliandra leaf meal with maximum level 5.0% did not affect the performance of broiler.